Development and validation of an educational technology for the prevention and treatment of pressure injuries - Leites , Elisandra; Silva, Patrícia Pedroso da; Pavinatto, Luisa; Moraes, Juliano Teixeira; Carvalho, Sidiclei Machado; Leal, Sandra Maria Cezar (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To develop and validate an educational technology designed for patients, family members, and caregivers focused on the prevention and treatment of pressure injuries. Method: This methodological study was conducted in three stages: 1) an integrative review (IR) that guided the development of the technology’s content; 2) the development of a website-based educational tool; and 3) content validation by experts, valuating both the content and the technology itself. Regarding the integrative review stage, research was conducted using the databases of the Virtual Health Library (Portuguese Acronym: BVS), the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (Portuguese Acronym: CAPES), and the Scientific Electronic Library Online (SciELO). Articles published between 2015 and 2019 were included. Experts for content evaluation were selected through convenience sampling, and validation was conducted using the Content Validity Index (CVI). Results: In the integrative review, ten articles and one guideline were selected. Two categories emerged from the analysis: pressure injury prevention and nutritional treatment, which guided the development of the educational technology titled “PreventPele”. The literature review also informed the development of care guidance tabs, a measurement scale, and sections on treatment-related products and technologies. Content validation was conducted by 12 expert judges, achieving a 95.2% agreement rate and an overall Content Validity Index (CVI) of 1. Conclusion: This study led to the development of an open-access website on pressure injury prevention designed for healthcare professionals, family members, and caregivers, offering validated, up-to-date, and high-quality information.